ANALISIS SEMIOTIKA RIFFATERRE DALAM PUISI DONGENG MARSINAH KARYA SAPARDI DJOKO DAMONO - Huri, Ranti Maretna; Hayati, Yenni; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2017)
The purposes of this study are to (1) describe the reading of heuristic and hermeneutic, (2) describe semantic indirection, (3) describe matrix, model, and variant, and (4) show hypogram from the poems of Dongeng Marsinah by Sapardi Djoko Damono. This is a qualitative descriptive study because the sources are from books and journals. The data are word, phrase, clause or sentences from the poems of Dongeng Marsinah by Sapardi Djoko Damono. The results are (1) the reading of heuristic and hermeneutic, (2) semantic indirection, (3) matrix, model, and variant, and (4) hypogram from the poems of Dongeng Marsinah by Sapardi Djoko Damono, which use the theory of Semiotic Riffaterre.Â Keywords: poem, Semiotics, Riffaterre